Sanskrit glossary of yogic terms [2nd ed.] - Yogakanti, Swami (Munger Yoga Publications Trust, 2016)
About the Book: Sanskrit Glossary of Yogic Terms This Sanskrit glossary contains a Wealth of definitions of Yogaand its related topics, including philosophies, Yogic Traditionsand concepts. It is designed to Aid yoga practioners who seek thedeeper Meaning of yogas symbols and metaphoric language. It may beutilized as a guide for understanding the precision and subtleassociations of Sanskrit words found in yoga publications. The Sanskrit glossary, with English translation, reveals thedeep significance of yogic terms through word structure, meaning,scriptural references and Original Devanagri script. Selectedpictures illustrate the text.
Keywords: Sanskrit language; Yoga